Institucionalização da bioética no Brasil: impactos na educação superior - Salgado, Rita de Cássia Falleiro (2016)
The thesis considers the context of Bioethics in the international and national scenario and its socio-political implications for the process of Institutionalization of Bioethics in Brazil and its impacts on Higher Education. The importance of this theme is emphasized when considering the social demand of this beginning of the century, in the perspective of a society in which human values dissipate amid the advances of globalization, making essential the humanistic formation guided by ethical values. The research problem is expressed in the guiding question: Why has Bioethics not been able to institutionalize in Brazil, as a curricular discipline in undergraduate courses in the area of health sciences in Higher Education? The general objective of the research was to analyze the Institutionalization of Bioethics in Brazil, considering its impacts to Higher Education. For this purpose, the following specific objectives of this study were chosen: To identify historical milestones of the international and national trajectory in the context of the public policies that determine the Institutionalization of Bioethics in Brazil; To understand the process of Institutionalization of Bioethics and the production of knowledge on the theme of Bioethics and Education; To investigate the Bioethics scenario in relation to undergraduate courses in the area of Health Sciences; To identify the presence of the discipline of Bioethics, characterizing the teaching of Bioethics in undergraduate courses in the area of Health Sciences of Curitiba. The methodology was carried out as documentar, exploratory and descriptive research, using quantitative and qualitative approaches. Data were collected from federal instances, such as: MEC, CNE, CES, SESu and Conaes, in addition to the DCN and the curricular matrix of undergraduate courses in Health Sciences, from IES recognized by MEC. We analyzed 14 Resolutions issued between 2001 and 2014, referring to undergraduate courses in the area of Health Sciences recognized by the MEC, to punctuate the descriptors, determined by the words: ethics, ethics/bioethics, or bioethics only. From this, the correlation between the frequency of words and the implications for the insertion of subjects related to Ethics and/or Bioethics in the curricular matrix was verified, it was verified that there is no proportionality in this correlation. In relation to the presence of the disciplines in undergraduate courses at IES that offer Post-Graduation in Bioethics, the analysis confirmed an expressive correlation, whereas IES encourage research related to the theme by offering subjects that contemplate the issues of Ethics and Bioethics in their graduations. It was found that disciplines named from the topic of study of Ethics are more common and usually obligatory, while those dedicated to the study of Bioethics are presented as electives and in smaller numbers. It is considered that, even in the face of the growing commitment of Brazilian society from the health professionals' movements, instigating public policies on health and education to the relevance of Bioethics as an area of knowledge, there is still a gap between the Laws granted and academic practice in the scope of curricular changes and their effectiveness. Therefore, it is necessary to continue research as an incentive to this field of knowledge: Bioethics and Education.